EVALUASI RASIO RENCANA ANGGARAN PELAKSANAAN DENGAN BIAYA RIIL PELAKSANAAN TERHADAP PENGARUH FLUKTUASI HARGA MATERIAL : (Studi Kasus: Pembangunan Gedung Lt. III (15 RKB, Tangga) SD N 3 Panjer, Kota Denpasar) - Ni Made Ratih Pradewi; I.A. Putu Sri Mahapatni; I Made Harta Wijaya (WidyaTeknik, 2026)
The construction sector plays a crucial role in supporting infrastructure development and regional economic growth, making project cost planning and control crucial. One of the documents used by contractors for cost control is the Implementation Budget Plan (RAP), which is prepared based on actual field conditions and actual material prices. However, in practice, discrepancies often occur between the RAP and actual costs due to material price fluctuations, which are influenced by economic factors, distribution, and field conditions. This study aims to evaluate the ratio of the RAP to actual implementation costs and analyze the effect of material price fluctuations on project cost changes for the construction of the third-floor building (15 RKB and stairs) at Panjer 3 Elementary School, Denpasar City. The research method used is descriptive quantitative with a comparative approach and simple linear regression analysis. The data used include the initial RAP, the RAP after fluctuations, and the actual project implementation costs, obtained from project documents and a field material price survey. The results of the study indicate a 4.657% increase in costs, with the initial RAP of Rp933,208,020.60 increasing to Rp978,792,243.89, a difference of Rp45,584,223.29. Therefore, adaptive cost control, regular unit price updates, and sound risk management are required to minimize the impact of fluctuations in project implementation.